1992
DOI: 10.1042/bj2830737
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin-specific inhibition by and slow cleavage of hirulog-1

Abstract: Hirulog-1 [D-Phe-Pro-Arg-Pro-[Gly]4-desulphohirudin-(53-64) (HV1)] was designed to bind by its first four and last 12 residues to the alpha-thrombin catalytic site and anion-binding exosite for fibrin(ogen) recognition respectively, with a [Gly]4 bridge and an Arg-Pro bond at the scissional position. Human alpha-, gamma- and zeta-thrombins, as well as bovine trypsin, readily hydrolyse Spectrozyme-TH (D-hexahydrotyrosyl-Ala-Arg p-nitroanilide) at pH 7.4 and approx. 23 degrees C. Both alpha- and zeta-thrombins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
64
1
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 53 publications
8
64
1
1
Order By: Relevance
“…Thrombin inhibitors are exposed to three types of proteases in vivo (1) thrombin, which forms complexes with the inhibitors and may hydrolyze them (DiMaio et al, 1990;Witting et al, 1992a;Szewczuk et al, 1993), (2) plasma proteases, which the inhibitors encounter in the circulation, and (3) proteases of the kidney, which are involved in the clearance of the peptides. The proteolytic stability of the inhibitor P448, dansyl-Arg-(D-Pip)-pAdodyAbu-DFEEIPEEYLQ-OH, was examined.…”
Section: Activementioning
confidence: 99%
See 1 more Smart Citation
“…Thrombin inhibitors are exposed to three types of proteases in vivo (1) thrombin, which forms complexes with the inhibitors and may hydrolyze them (DiMaio et al, 1990;Witting et al, 1992a;Szewczuk et al, 1993), (2) plasma proteases, which the inhibitors encounter in the circulation, and (3) proteases of the kidney, which are involved in the clearance of the peptides. The proteolytic stability of the inhibitor P448, dansyl-Arg-(D-Pip)-pAdodyAbu-DFEEIPEEYLQ-OH, was examined.…”
Section: Activementioning
confidence: 99%
“…The crystal structure of PPACK-thrombin (Bode et al, 1989) suggested that D-PhePro-Arg in the bivalent inhibitors binds to the thrombin active site in the substrate binding mode, where Arg-X is the scissile peptide bond. In fact, the active site blocking moiety, D-Phe-Pro-Arg-Pro, of the bivalent inhibitors was hydrolyzed slowly at Arg-Pro peptide bond (DiMaio et al, 1990;Witting et al, 1992a;Szewczuk et al,1993). The arginine and benzamidine-based thrombin inhibitors such as MD-805, NAPAP, and TAPAP are other types of active site inhibitors (Okamoto et al, 1980(Okamoto et al, , 1981Kikumoto et al, 1980aKikumoto et al, ,b, 1984Stiirzebecher et al, 1983Stiirzebecher et al, , 1984.…”
mentioning
confidence: 99%
“…The Ki and Kd values were determined for a-thrombin by tight binding and consumptive inhibitor methods, as described (22,23).…”
mentioning
confidence: 99%
“…98 Unlike hirudin, bivalirudin produces only transient inhibition of the active site of thrombin, because, once bound, thrombin cleaves the Pro-Arg bond within the amino-terminal of bivalirudin. 99,100 Without its aminoterminal segment, the carboxy-terminal portion of bivalirudin bound to thrombin's substrate recognition site is a much weaker thrombin inhibitor. 99 Consequently, substrates can compete with cleaved bivalirudin for access to exosite 1.…”
Section: Bivalirudinmentioning
confidence: 99%
“…99,100 Without its aminoterminal segment, the carboxy-terminal portion of bivalirudin bound to thrombin's substrate recognition site is a much weaker thrombin inhibitor. 99 Consequently, substrates can compete with cleaved bivalirudin for access to exosite 1. Bivalirudin's plasma half-life after intravenous infusion is 25 minutes.…”
Section: Bivalirudinmentioning
confidence: 99%